Pattern of Ocular Injuries in a District Hospital of Bangladesh (Medicine Today, 2024)
Introduction: Ocular injuries are one of the leading causes of visual morbidity in our country. Our present study aims to evaluate the pattern of ocular injuries in a District Hospital. Materials and Methods: This was a prospective observational study, conducted by ophthalmology department of Sherpur District sadar hospital, Bangladesh. The study was done from January 2023 to June 2023. Results: The sample size was 100. All age’s group and both sexes were selected randomly in this study. The history of the patient regarding particulars of the patient, time of injury, place where it occurs, type of object, nature of injury and visual acuity at presentation was recorded. Most of the patients were 11-20 years age group (44 %). 82 % of the patients were male and 18 % were female. Patients were mostly from low socioeconomic group (65%). 35% patients attended hospital within 6 hours of injury. Type of the injury was accidental most commonly (88 %) and of them occupational was the majority (54 %), homicidal injuries were 12 %. Sharp objects causes 55 %, blunt trauma causes 35% of injuries. 65% of patients had open globe injury and 35 % had closed globe injuries. Most of the patients (62 %) had visual acuity 6/60 to PL at the time of admission. Conclusion: Our study reviled that young males of low socioeconomic group affected more and with sharp objects and are mainly occupational in nature.Medicine Today 2023 Vol.36 (1): 23-25